Prevalence of Helicobacter pylori in peptic ulcer perforation - John, Binni; P. Mathew, Bipin; Chandran C., Vipin (International Surgery Journal, 2017)
Background: Helicobacter pylori have an important role in the pathogenesis of peptic ulcer disease. The aim of the present study was to observe the prevalence of H. pylori in peptic ulcer perforation cases and the rationale of H. pylori eradication therapy post operatively and to investigate factors associated with peptic ulcer. Methods: This cross-sectional study was conducted at the Department of general surgery, Government Medical College, Kottayam for a period 20 months from March 2012 to October 2013 after getting approval from institutional ethics committee. A total of 113 patients were participated in the study after meeting inclusion criteria. After getting written consent from the patients with perforated peptic ulcer, resuscitation and laparotomy was performed in the emergency department. H. pyloriinfection was confirmed by histopathological examination by Giemsa staining. Based on the histopathological report, the prevalence of H. pylori infection in the patients was assessed and was given appropriate H. pylori eradication regimen. Results: The mean age of presentation of the patients was 52.81±14.5 years. Male to female ratio was 4.14:1. Out of 113 cases, 67 cases (59.3%) had duodenal ulcer perforation while 46 cases (40.7%) had gastric ulcer perforation. Of them 53(46.9%) cases were positive H. pylori positive. No significant association was found between the incidence of H. pylori infection in peptic ulcers with smoking, hypertension, diet intake, NSAIDS intake. In our study association between H. pylori and diabetes mellitus (p=0.02) found to be significant which can be further investigated. Conclusion: According to our study the prevalence of H. pylori infection in perforated peptic ulcer disease is 47% which must be considered as significant. Hence all the patients undergoing laparotomy for peptic ulcer perforation should be investigated for H. pylori infection and if positive we must start the anti H. pylori regimen for them, which is more cost effective.